2010
DOI: 10.1111/j.1365-2842.2010.02094.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trials in zirconia: a systematic review

Abstract: Zirconia is unique in its polymorphic crystalline makeup, reported to be sensitive to manufacturing and handling processes, and there is debate about which processing method is least harmful to the final product. Currently, zirconia restorations are manufactured by either soft or hard-milling processes, with the manufacturer of each claiming advantages over the other. Chipping of the veneering porcelain is reported as a common problem and has been labelled as its main clinical setback. The objective of this sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
304
1
38

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(347 citation statements)
references
References 49 publications
4
304
1
38
Order By: Relevance
“…One explanation is the inclusion of patients with signs of bruxism who are often excluded from clinical studies [29,30]. Typically, these patients severely abraded their occlusal surfaces and provoked critical ceramic fractures with exposures of the zirconia cores.…”
Section: Discussion Survival Estimatesmentioning
confidence: 99%
“…One explanation is the inclusion of patients with signs of bruxism who are often excluded from clinical studies [29,30]. Typically, these patients severely abraded their occlusal surfaces and provoked critical ceramic fractures with exposures of the zirconia cores.…”
Section: Discussion Survival Estimatesmentioning
confidence: 99%
“…Recently, review report by Al-Amleh et al 19) showed that chipping of the veneering porcelain is confirmed to be an ongoing problem with zirconia all-ceramic-based restorations. At the beginning of introduction of zirconia restorations, uniform thickness coping was used.…”
Section: Discussionmentioning
confidence: 99%
“…Y 2 O 3 (approximately 3 mol%) is the most widely used stabilizer for dental zirconia (Y-TZP) [2]. In response to mechanical stimuli such as tensile stress at the crack tips, the stabilized tetragonal zirconia transforms to the more stable monoclinic phase with a local increase in volume of approximately 4-5 vol% [10]. This increase in volume closes the crack tips, effectively blunting crack propagation [10].…”
Section: Introductionmentioning
confidence: 99%
“…In response to mechanical stimuli such as tensile stress at the crack tips, the stabilized tetragonal zirconia transforms to the more stable monoclinic phase with a local increase in volume of approximately 4-5 vol% [10]. This increase in volume closes the crack tips, effectively blunting crack propagation [10]. It is this transformation-toughening process, which gives zirconia its strength and toughness, exceeding all currently available dental ceramics [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation